Sleep education during pregnancy for new mothers - Kempler Liora; Sharpe Louise; Bartlett Delwyn (BMC, 2012)
Abstract Background There is a high association between disturbed (poor quality) sleep and depression, which has lead to a consensus that there is a bidirectional relationship between sleep and mood. One time in a woman's life when sleep is commonly disturbed is during pregnancy and following childbirth. It has been suggested that sleep disturbance is another factor that may contribute to the propensity for women to become depressed in the postpartum period compared to other periods in their life. Post Natal Depression (PND) is common (15.5%) and associated with sleep disturbance, however, no studies have attempted to provide a sleep-focused intervention to pregnant women and assess whether this can improve sleep, and consequently maternal mood post-partum. The primary aim of this research is to determine the efficacy of a brief psychoeducational sleep intervention compared with a control group to improve sleep management, with a view to reduce depressive symptoms in first time mothers. Method This randomised controlled trial will recruit 214 first time mothers during the last trimester of their pregnancy. Participants will be randomised to receive either a set of booklets (control group) or a 3hour psychoeducational intervention that focuses on sleep. The primary outcomes of this study are sleep-related, that is sleep quality and sleepiness for ten months following the birth of the baby. The secondary outcome is depressive symptoms. It is hypothesised that participants in the intervention group will have better sleep quality and sleepiness in the postpartum period than women in the control condition. Further, we predict that women who receive the sleep intervention will have lower depression scores postpartum compared with the control group. Discussion This study aims to provide an intervention that will improve maternal sleep in the postpartum period. If sleep can be effectively improved through a brief psychoeducational program, then it may have a protective role in reducing maternal postpartum depressive symptoms. Registration details This trial is registered with the Australian New Zealand Clinical Trials Register under the registration number ACTRN12611000859987